Genomic diagnosis implementation in a pediatric hospital: Preliminary results - Scaglia, Paula Alejandra (2019)
The access to new technologies, like Next Generation Sequencing (NGS) and microarray, has allowed the development of effective high-performance diagnosis algorithms for genetic pediatric diseases. The aim of this work was to establish standardized procedures for genomic diagnosis of genetic pediatric diseases in a pediatric hospital. Patients with presumptive diagnoses of genetic diseases (intellectual disability, metabolic, hematological or immune diseases or delay of growth and puberty) were included. DNA from peripheral blood was obtained from the patients and their parents. Genomic diagnosis procedures were performed by NGS (Clinical exome, TruSight One, NextSeq 500 Illumina) and microarray studies (8x60K Platform, Agilent). NGS results were analyzed by own designed bioinformatic pipelines, and B platform (Bitgenia) was used to prioritize variants. All variants found (sequence changes or Copy Number Variations) were classified according to American College of Medical Genetics and Genomics recommendations. This study was approved by the hospital ethical review board. Diagnostic flowchart was implemented according to designed operative protocols. Patients referred by specialized pediatricians were evaluated by the interdisciplinary team to agree on the best diagnostic pathway. From March 2018 to August 2019, 200 probands were included (86 with delay of growth and puberty, 12 hematologic, 4 immunologic and 55 metabolic disorders and 43 with intellectual disability). Among the 36 cases studied by microarray, 5 pathogenic variants (13.9 %), and 3 variants of uncertain significance were found. In 24 of the 60 patients (40 %) studied by NGS, genic variants related to patient?s phenotype were found. Conclusion: Interdisciplinary team work has enabled the successful implementation of these new genomic diagnosis techniques in the hospital. Diagnosis efficiency achieved agrees with international standards.